Kimura’s Disease in Unusual Anatomical Locations: Clinical and Radiological Characteristics - Xie W; Luo J; Tang R; Zhou X; Wang X; Wang G; Zhang Y (Dove Medical Press, 2024)
Weiwei Xie,1,* Junqi Luo,1,* Ruowei Tang,2,* Xuan Zhou,3 Xiaohong Wang,4,5 Guojie Wang,1,5 Yaqin Zhang1 1Department of Radiology, the Fifth Hospital of Sun Yat-sen University, Zhuhai, Guangdong Province, People's Republic of China; 2Department of Radiology, Beijing Friendship Hospital, Beijing, People's Republic of China; 3Departments of Pathology, The Fifth Affiliated Hospital of Sun Yat-Sen University, Zhuhai, Guangdong Province, People's Republic of China; 4Department of Radiology, the Third Hospital of Sun Yat-sen University, Guangzhou, Guangdong Province, People's Republic of China; 5Department of Radiology, The First People's Hospital of Kashi Prefecture, Kashi Prefecture, Xinjiang Uygur Autonomous Region, People's Republic of China*These authors contributed equally to this workCorrespondence: Yaqin Zhang; Guojie Wang, Department of Radiology, the Fifth Hospital of Sun Yat-sen University, 52 East Meihua Road, Xiangzhou District, Zhuhai, Guangdong Province, People's Republic of China, Email zhyaqin@mail.sysu.edu.cn; wanggj5@mail.sysu.edu.cnPurpose: To explore the clinical and imaging features of rare site Kimura's disease (KD).Methods: Retrospective analysis was conducted on the clinical manifestations, laboratory examinations, and imaging features of five patients with rare site KD. All imaging data, including the location, quantity, size, uniformity, boundary, and enhanced appearance of the lesion were evaluated by two independent radiologists.Results: Of the five patients, four were asymptomatic, and one experienced localized skin itching. Four cases involved subcutaneous nodules in the upper arm, while one was in the inguinal region. The main manifestations were single (three cases) or multiple (two cases) subcutaneous nodules/masses, with three patients accompanied by local lymph node enlargement. Four patients exhibited elevated eosinophil counts in their peripheral blood. Four patients had lesions with vascular flow voids; in three of these, the lesions also showed prominent enhancement. Notably, the lesion in a 5-year-old did not show vascular flow voids but displayed significant enhancement. Additionally, two patients showed edema around the lesions.Conclusion: The presence of solitary or multiple subcutaneous nodules/masses in the upper arm or inguinal area, accompanied by lymph node enlargement, elevated eosinophils in the peripheral blood, and the observation of internal vascular within the lesion, can aid in the diagnosis of KD occurring in uncommon anatomical locations.Keywords: Kimura disease, increased eosinophils, image, uncommon anatomical locations